Selection of Suitable Prodrug Candidates for in vivo Studies via in vitro Studies; The Correlation of Prodrug Stability in Between Cell Culture Homogenates and Human Tissue Homogenates - Tsume, Yasuhiro; Amidon, Gordon L (Journal of Pharmacy & Pharmaceutical Sciences, 2012)
Purpose. To determine the correlations/discrepancies of drug stabilities between in the homogenates of human culture cells and of human tissues. Methods. Amino acid/dipeptide monoester prodrugs of floxuridine were chosen as the model drugs. The stabilities (half-lives) of floxuridine prodrugs in human tissues (pancreas, liver, and small intestine) homogenates were obtained and compared with ones in cell culture homogenates (AcPC-1, Capan-2, and Caco-2 cells) as well as human liver microsomes. The correlations of prodrug stability in human small bowel tissue homogenate vs. Caco-2 cell homogenate, human liver tissue homogenate vs. human liver microsomes, and human pancreatic tissue homogenate vs. pancreatic cell, AsPC-1 and Capan-2, homogenates were examined. Results. The stabilities of floxuridine prodrugs in human small bowel homogenate exhibited the great correlation to ones in Caco-2 cell homogenate (slope = 1.0-1.3, r2 = 0.79-0.98). The stability of those prodrugs in human pancreas tissue homogenate also exhibited the good correlations to ones in AsPC-1 and Capan-2 cells homogenates (slope = 0.5-0.8, r2 = 0.58-0.79). However, the correlations of prodrug stabilities between in human liver tissue homogenates and in human liver microsomes were weaker than others (slope = 1.3-1.9, r2 = 0.07-0.24). Conclusions. The correlations of drug stabilities in cultured cell homogenates and in human tissue homogenates were compared. Those results exhibited wide range of correlations between in cell homogenate and in human tissue homogenate (r2 = 0.07 – 0.98). Those in vitro studies in cell homogenates would be good tools to predict drug stabilities in vivo and to select drug candidates for further developments. In the series of experiments, 5′-O-D-valyl-floxuridine and 5′-O-L-phenylalanyl-L-tyrosyl-floxuridine would be selected as candidates of oral drug targeting delivery for cancer chemotherapy due to their relatively good stabilities compared to other tested prodrugs. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.